2018
DOI: 10.1088/1748-0221/13/10/t10004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a cryogenic baffle system on the suppression of radon-induced background in the KATRIN Pre-Spectrometer

Abstract: A : The KATRIN experiment will determine the effective electron anti-neutrino mass with a sensitivity of 200 meV/c 2 at 90% CL. The energy analysis of tritium β-decay electrons will be performed by a tandem setup of electrostatic retarding spectrometers which have to be operated at very low background levels of < 10 −2 counts per second. This benchmark rate can be exceeded by background processes resulting from the emanation of single 219,220 Rn atoms from the inner spectrometer surface and an array of non-eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Recent studies have shown that an elevated background can strongly affect the KATRIN sensitivity. KATRIN successfully applied methods to reduce radon-induced backgrounds [195], however, further measures are needed and are being explored to reach the design background rate of 10 mcps.…”
Section: Katrinmentioning
confidence: 99%
“…Recent studies have shown that an elevated background can strongly affect the KATRIN sensitivity. KATRIN successfully applied methods to reduce radon-induced backgrounds [195], however, further measures are needed and are being explored to reach the design background rate of 10 mcps.…”
Section: Katrinmentioning
confidence: 99%
“…A fraction of the background arises from Rn-219 and Rn-220 decays in the volume of the main spectrometer and subsequently magnetically stored electrons. Through ionization of residual gas, this primary stored electrons creates numerous low-energy secondary electrons, which can reach the detector and create background [27,[54][55][56][57]. These background events are correlated in time, and hence the total background rate is not Poisson distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its origin from a small number of 219 Rn decays, this background results in extended time periods where the background level is enhanced yielding a small non-Poissonian component [43]. Liquid-nitrogen cooled copper baffles at the inlet of the NEG pumps act as a countermeasure [44]. The coverage of the inner surface of the main spectrometer with a monolayer of H 2 O, originating from an imperfect bake out of the prespectrometer, has led to the formation of a thin layer of H 2 O covering the baffle surface.…”
mentioning
confidence: 99%